High-strength and high-toughness fine-grain complex-phase structure wear-resistant steel and preparation method thereof
By designing high-strength and tough fine crystal composite structure in wear-resistant steel and adopting a specific heat treatment process, the problem of insufficient low-temperature toughness of wear-resistant steel is solved, and high impact absorption work is achieved in an environment below -40℃.
Patent Information
- Application Number
- CN202411728160.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-14
AI Technical Summary
Wear-resistant steel has poor toughness in low-temperature environments, especially under conditions below -40℃, and breaking is prone to occur.
The preparation method of high-strength and tough fine crystal composite structure wear-resistant steel is adopted, and through reasonable chemical composition design and heat treatment process, a complex structure of 93%~96% tempered martensite, 3%~5% residual austenite and 1%~2% carbide is formed.
While maintaining high strength and high hardness, the low-temperature toughness of wear-resistant steel is significantly improved, and the impact absorption work of steel plate -40℃ is ≥48J.
Smart Images

Figure CN119614998A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of steel smelting, and in particular to a high-strength and toughness fine-grained multiphase structure wear-resistant steel and a preparation method thereof. Background Art
[0002] Low alloy wear-resistant steel is a special steel material that has good toughness and machinability while maintaining a certain strength and hardness. This type of steel usually contains a small amount of alloying elements, such as manganese, chromium, molybdenum, etc. The addition of these elements can significantly improve the wear resistance of the steel while maintaining its good weldability and cold bending properties. Low alloy wear-resistant steel is suitable for mining machinery, construction machinery, transportation and other fields, especially in those occasions that need to withstand high wear and impact loads.
[0003] Low-alloy wear-resistant steel, with its low cost and high wear resistance, can resist the damage to the workpiece caused by wear and impact to a large extent, and extend the service life of mechanical equipment. In the field of engineering machinery, it is widely used to manufacture bulldozer blades, loader buckets, outer guard plates and inner liners of electric shovel buckets, bucket edges and blades of wheel excavators, scrapers for automatic loading and unloading mining vehicles, and bottom liners of conveyor troughs. Many other key wear-resistant parts of engineering machinery have broad application prospects.
[0004] Toughness is an important performance indicator of high-hardness wear-resistant steel to resist fracture. At present, wear-resistant steel workpieces in engineering machinery, such as bulldozer blades, are very likely to break due to low toughness when colliding with hard rock materials during operation; and in the service environment of high latitudes and high altitudes in winter gravel and frozen soil, the toughness of wear-resistant steel deteriorates as the temperature decreases.
[0005] Therefore, improving the hardness of wear-resistant steel while ensuring good toughness (especially -40°C low-temperature impact toughness) has always been an urgent need of the industry and one of the important directions for the development of wear-resistant steel. Summary of the invention
[0006] In order to solve the technical problem of poor low-temperature toughness of wear-resistant steel, the present invention provides a high-strength and toughness fine-grained multiphase wear-resistant steel and a preparation method thereof. The prepared wear-resistant steel has high strength, high hardness and good low-temperature toughness, and the steel plate has an impact absorption energy of ≥48J at -40°C.
[0007] In a first aspect, the present invention provides a wear-resistant steel with a high-strength and high-toughness fine-grained duplex structure, comprising chemical components in the following weight percentages: C 0.12% - 0.20%, Si 0.1% - 0.4%, Mn 1.6% - 2.0%, Ti 0.045% - 0.08%, Cr 0.15% - 0.3%, Mo 0.05% - 0.16%, Al 0.02% - 0.05%, P ≤ 0.01%, S ≤ 0.003%, N ≤ 0.002%, H ≤ 0.0002%, B 0.002% - 0.004%, where (30C + 0.5Mn) × 100 ≥ 4.4, B / S ≥ 3, 0.3 ≤ Ti / Mo ≤ 0.6, and the balance is Fe and inevitable impurity elements.
[0008] Furthermore, the obtained wear-resistant steel with a high-strength and high-toughness fine-grained duplex structure has the following mechanical properties: the surface Brinell hardness is 435 - 470 HBW, and the hardness attenuation from the surface to the core in the thickness direction of the steel plate is ≤ 2 HBW / cm; the tensile strength of the steel plate is 1300 - 1400 MPa, the yield ratio is ≤ 0.82, and the elongation after fracture is ≥ 12%; the corresponding relationship between the impact absorption energy of the steel plate at -40°C and the thickness h of the finished steel plate is as follows: when 12 mm ≤ h ≤ 20 mm, the impact absorption energy of the steel plate at -40°C is ≥ 75 J; when 20 mm < h ≤ 28 mm, the impact absorption energy of the steel plate at -40°C is ≥ 64 J; when 28 mm < h ≤ 36 mm, the impact absorption energy of the steel plate at -40°C is ≥ 56 J; when 36 mm < h ≤ 42 mm, the impact absorption energy of the steel plate at -40°C is ≥ 48 J.
[0009] The basis for the types and contents of the alloying elements in the present invention is as follows: Carbon (C) is the most important element affecting the hardness, strength, and toughness of tempered martensite in the room-temperature structure of wear-resistant steel. Although the carbon content determines the hardness of martensite, that is, the higher the carbon content, the higher the hardness of martensite, when the carbon content exceeds 0.2% (C > 0.2%), the morphology of martensite will gradually change from lath to fine plate-like, and its substructure will change from dislocation to twin, which will seriously damage the toughness of the steel. Therefore, the carbon content in the wear-resistant steel described in the present invention is ≤ 0.20%, and the limitation of the solution strengthening effect due to the reduction of the carbon content will be compensated by the grain refinement achieved by multiple phase transformations proposed in the present invention. The carbon (C) content is designed to be 0.12% - 0.20%.
[0010] Silicon (Si) plays a deoxidizing role during smelting through the addition of ferrosilicon, etc., purifying the molten steel. Besides dissolving in the matrix to play a solution strengthening role, silicon also has a strong effect of inhibiting the diffusion of carbon elements during cooling and tempering, thus can inhibit the excessive growth of carbides and promote the formation of retained austenite, thereby improving the toughness of the steel. The silicon (Si) content is designed to be 0.1% - 0.4%.
[0011] Manganese (Mn) is deoxidized by adding ferromanganese and silicon-manganese alloy during the smelting process. As an austenite forming and stabilizing element, manganese can strongly increase the hardenability of steel, reduce the transformation temperature of steel and the critical cooling rate of steel, and increase the volume fraction of retained austenite in the room temperature structure. However, when the Mn content in the steel is too high, it is easy to cause segregation and grain coarsening in the ingot, and increase the temper brittleness sensitivity of the steel. Based on this, in the wear-resistant steel described in the present invention, the mass percentage of manganese is controlled between 1.6% and 2.0%.
[0012] Titanium (Ti) has a strong affinity with carbon, nitrogen and sulfur, and the formed compounds are highly stable. Only when heated to above 1000°C will it slowly dissolve into the solid solution of iron. Carbonitride particles containing Ti can effectively inhibit the coarsening of austenite grains, but too much titanium can easily lead to the formation of TiN cubes with sharp edges and corners and a large amount of titanium carbide (TiC). The formation of too much titanium carbide will reduce the hardenability of steel. Therefore, the content of titanium in the wear-resistant steel described in the present invention is 0.045%≤Ti≤0.08%.
[0013] Chromium (Cr), as a strong carbide-forming element, can significantly improve the wear resistance and hardenability of steel. However, too high a chromium content will increase the tendency of dendritic segregation and temper brittleness in the steel and deteriorate the welding quality. Therefore, the chromium content in the wear-resistant steel of the present invention is 0.15% to 0.3%.
[0014] Molybdenum (Mo) can exist in the solid solution phase and carbide phase in steel, which can improve the hardenability of steel, inhibit the temper brittleness caused by alloy elements such as manganese and chromium, and improve the tempering stability of steel. Based on this, the content of molybdenum in the wear-resistant steel of the present invention is 0.05%~0.16%.
[0015] Titanium (Ti) and molybdenum (Mo) are added to the steel at the same time. Molybdenum can effectively promote the nucleation of TiC particles and inhibit their growth, thereby forming a nanoscale (Ti, Mo)C precipitation phase with stronger resistance to coarsening. Based on the effect of molybdenum on reducing the diffusion rate of carbon in austenite, the formation of larger, nearly square, and sharp-edged titanium and molybdenum carbonitrides is suppressed by controlling the titanium and molybdenum content ratio (i.e., 0.3≤Ti / Mo≤0.6).
[0016] Carbon (C) and manganese (Mn) are austenite-forming and stabilizing elements in steel. By controlling the overall content of the two elements, that is, (30C+0.5Mn)×100≥4.4, the transformation temperature of the steel, the volume fraction of retained austenite in the room temperature structure and its stability can be adjusted, thereby improving the toughness of the steel based on the principle of deformation-induced phase transformation.
[0017] Aluminum (Al) is used as a deoxidizing and nitrogen fixing agent during steelmaking. It can combine with nitrogen, not only eliminating the harm of nitrogen, but also forming AlN to hinder the recrystallization of austenite during hot working, thereby refining the grains. The addition of aluminum can also increase the martensite transformation temperature. However, when too much aluminum is added to the steel, non-metallic inclusions are easily formed, and the precipitated AlN is coarsened, which not only loses the function of refining the grains, but also a large amount of AlN accumulates at the grain boundaries during hot working and becomes the main crack source. Therefore, the content of aluminum in the wear-resistant steel of the present invention is 0.02% to 0.05%.
[0018] Phosphorus (P), sulfur (S), nitrogen (N) and hydrogen (H) as impurity elements affect the plasticity and toughness of steel. The present invention controls P≤0.01%, S≤0.003%, N≤0.002%, and H≤0.0002%.
[0019] Boron (B) has a strong grain boundary segregation effect, but excessive boron (B) forms carbon-boron compounds, which deteriorates the toughness of martensitic steel after quenching. As an impurity element, the present invention controls the B content to be below 0.0004%.
[0020] Furthermore, the obtained high-strength and toughness fine-grained multiphase wear-resistant steel has the following microstructure: 93% to 96% tempered martensite + 3% to 5% retained austenite + 1% to 2% carbide, wherein the tempered martensite lath width is ≤0.5 μm; the retained austenite is mostly in the form of a film, a small amount is in the form of a block, and the width of the retained austenite film is ≤0.1 μm; the carbides are mainly cementite, Cr carbide, Ti-containing carbide and Ti-containing carbonitride, including one of the above precipitates or multiphase but not limited thereto; wherein, there are mainly two categories of Ti-containing carbides and Ti-containing carbonitrides, one is Ti-rich and low-Mo carbonitrides, which are approximately square, relatively large in size, with an average particle size of 0.25-1.0 μm, relatively small in number, and mostly distributed at the original austenite grain boundaries; the other is Ti and Mo composite precipitated carbides, which are in the form of thin flakes, short rods or approximately spheres, relatively small in size, with an average particle size of about 3-200 nm, relatively large in number, and dispersed throughout the tempered martensite matrix.
[0021] Furthermore, the insulation time is 0.6h+0~20min, where h is the thickness of the finished steel plate.
[0022] The crack arrestability, i.e., high toughness, of the wear-resistant steel obtained by the present invention is derived from the microstructural design of the material. The steel plate as a whole is composed of fine and uniform martensitic laths, and the fine matrix structure is the basis for the wear-resistant steel to simultaneously meet high hardness and high toughness. The Ti-containing carbonitride formed by the wear-resistant steel in the high temperature range, although slightly large in size, can effectively inhibit the excessive growth of austenite grains during heating and rolling by pinning the grain boundaries, thereby obtaining a smaller-sized martensitic matrix after quenching due to the hereditary nature of the organization. At the same time, a small amount of residual austenite in the martensitic matrix after phase transformation will transform into martensite under impact load, thereby increasing the impact absorption energy of the steel plate and achieving toughness improvement. Nano-precipitates, such as cementite, Cr-containing carbides, and Ti and Mo composite carbides, are dispersedly distributed in the tempered martensitic matrix. During the crack propagation process, the mutual entanglement with dislocations can easily form dislocation plugging, thereby hindering the propagation of cracks and having good crack arrestability.
[0023] In the second aspect, the present invention provides a method for preparing high-strength and toughness fine-grained multiphase wear-resistant steel, comprising the steps of smelting, continuous casting, heating, rolling, cooling and heat treatment in sequence; the heat treatment step adopts a quenching + low-temperature self-tempering process: the quenching comprises first heating the steel plate to 500-600°C, and then heating to 820-835°C at a rate of ≥60°C / min for heat preservation, so that the steel plate regenerates the nucleation and crystallization of austenite on the martensite matrix, and by controlling the heating rate and the heat preservation time in the high temperature range, the excessive growth of the grains of the steel plate during the reverse transformation of austenite is avoided, thereby completing the primary refinement of the high-temperature austenite structure of the steel plate (analogous to the hot rolling state), and then Cooling at a speed of ≥40℃ / s to 260~280℃, i.e. the critical interval of the martensitic transformation end temperature Mf point, allows the wear-resistant steel to further refine the organization through the martensitic phase transformation during the second quenching while retaining a certain amount (3%~5%) of residual austenite; then, air-cooling from this temperature to room temperature; low-temperature self-tempering is to complete the low-temperature self-tempering process of the steel plate using its own residual heat after quenching. In this process, carbides (including cementite, Cr-containing carbides, Ti, Mo composite carbides) are dispersed and precipitated in smaller sizes on the defects retained by quenching and the dislocation substructure (such as dislocation entanglement) inside the martensite, and then the steel plate is straightened, finished, sprayed, marked, and sampled for performance inspection.
[0024] Furthermore, the smelting process route is: molten iron KR desulfurization pretreatment → top and bottom double blowing converter smelting → LF refining → RH furnace vacuum refining; the RH process requires a processing time of not less than 12 minutes under a vacuum degree ≤ 1mbar. In order to minimize the content of gases and inclusions such as O, H, N in the molten steel, the pure degassing time is not less than 9 minutes.
[0025] Furthermore, the superheat of the tundish in the continuous casting process is controlled at 12 - 25°C, and casting is carried out under full protection to prevent secondary oxidation of the molten steel. The target value of the casting machine drawing speed is 0.85 - 1.35 m / min, with fluctuations controlled within ±0.1 m / min. By controlling the superheat and drawing speed, the quality of the cast slab is improved and the internal microstructure of the cast slab is refined; the liquid level fluctuation during the casting process is controlled within ±0.2 mm, and electromagnetic stirring of the mold is adopted to reduce the enrichment of Ti and N elements and inhibit the coarsening growth of large titanium nitrides; the dynamic soft reduction technology is adopted in the continuous casting process: starting from a solid fraction of 0.65 in the center of the cast slab, soft reduction is carried out with an initial reduction rate of 0.8 - 1.2 mm / m, and the reduction rate is dynamically increased at a rate of 0.04 - 0.06 mm / m according to the superheat and drawing speed of casting until the end of solidification, with a reduction amount of 2 - 8 mm, so as to improve the quality of the cast slab by controlling segregation, porosity, etc. without causing internal cracks in the cast slab. The thickness of the cast slab is 270 - 320 mm, and the ratio of the cast slab thickness to the final rolling thickness of the finished steel plate is ≥7.5. The cast slabs are stacked in a slow cooling pit and slowly cooled for more than 48 h.
[0026] Furthermore, in the heating process, the residence time of the cast slab in the furnace is 1.1t min + 20 - 30 min (t is the value of the cast slab thickness. If the cast slab thickness is 280 mm, then t = 280), and the cast slab is heated at a temperature range of 1200 - 1260°C for 40 - 45 min to ensure that the added alloying elements are fully dissolved and diffused in the steel while avoiding excessive grain growth.
[0027] Furthermore, the rolling process adopts a rolling mode of rough rolling + finish rolling. The rough rolling starting temperature is 1140 - 1180°C. The rough rolling stage adopts a rolling method of horizontal and vertical rolling, and a large reduction mode is adopted during the rolling process of 2 - 6 passes, with the reduction rate of each pass maintained at 16% - 30% to ensure sufficient driving force for dynamic recrystallization nucleation of austenite during rough rolling. The ratio of the thickness of the intermediate billet after rough rolling to the final rolling thickness of the finished steel plate is ≥3.2; after the intermediate billet is held at temperature for 3 - 12 s, it is sprayed with high-pressure water from the rack to rapidly cool down and enter the finish rolling while fully refining austenite. Among them: when the finished thickness is h and 12 mm ≤ h ≤ 28 mm, the finish rolling starting temperature of the steel plate is 980 - 1000°C, and the finish rolling final temperature is 850 - 870°C; when 28 mm < h ≤ 4 mm, the finish rolling starting temperature of the steel plate is 910 - 930°C, and the finish rolling final temperature is 830 - 850°C. During the process of rolling the intermediate billet to the finished thickness by using single-stand reciprocating rolling or multi-stand hot continuous rolling, it is ensured that the reduction rates of the last pass and the pass before the last pass are respectively ≥12% and ≥18%. In this way, due to the large accumulated deformation experienced in the non-recrystallized zone, a large number of dislocations and deformation bands are generated inside the austenite grains, which greatly increases the nucleation sites and the start point of the phase transformation (i.e., the Ms point) of the martensite phase transformation, is conducive to the progress of the martensite phase transformation, and makes the martensite lath spacing decrease and the lath bundle shorten after the phase transformation.
[0028] Furthermore, the cooling process adopts an online water cooling accelerated cooling method. By virtue of the cooling process and the targeted steel plate thickness specification (i.e. 12~42mm), the steel plate can obtain the target microstructure by high-temperature quenching while still maintaining a good plate shape. The starting temperature of online water cooling is ≥820℃, the final cooling temperature is ≤240℃, and the cooling rate is ≥40℃ / s, so that the steel plate is transformed from a fully austenite state to martensite, and the nucleation rate of the martensitic phase transformation is increased by the high cooling rate, thereby achieving the refinement of the internal microstructure of the steel plate. The steel plate is then air-cooled or stacked to room temperature to release the internal stress of the steel plate caused by online quenching.
[0029] The beneficial effect of the present invention is that the present invention can reduce the use of precious metal elements, and based on the addition and combination of austenite forming and stabilizing elements (i.e. C, Mn) and strong carbide forming elements (i.e. Ti, Mo), the gradual refinement of the internal microstructure of the steel plate is achieved in the cyclic phase transformation process control of low-temperature hot rolling, post-rolling quenching-quenching heat treatment, that is, through the comprehensive utilization of alloying component design and deformation heat treatment process, the precipitation of carbides and the deformation, recrystallization and phase transformation of austenite are effectively controlled, so as to obtain a refined and enhanced tempered martensite + residual austenite + carbide complex phase structure, so that the produced wear-resistant steel has high strength, high hardness and good low-temperature toughness, and the steel plate -40°C impact absorption energy is ≥48J. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0031] Figure 1 This is a scanning electron microscope photograph of the wear-resistant steel prepared in Example 1 of the specific implementation manner of the present invention.
[0032] Figure 2 This is a transmission electron microscope photo of the wear-resistant steel prepared in Example 1 of the specific implementation manner of the present invention.
[0033] Figure 3 This is a scanning electron microscope photograph of the wear-resistant steel prepared in Example 2 of the specific implementation manner of the present invention.
[0034] Figure 4 This is a transmission electron microscope photo of the wear-resistant steel prepared in Example 2 of the specific implementation mode of the present invention. DETAILED DESCRIPTION
[0035] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0036] Example 1 A high-strength and toughness fine-grained multiphase wear-resistant steel, comprising the following chemical components in weight percentage: C: 0.18%, Si: 0.3%, Mn: 1.8%, Ti: 0.07%, Cr: 0.28%, Mo: 0.14%, Al: 0.04%, P: 0.005%, S: 0.001%, N: 0.0017%, H: 0.00015%, B: 0.0035%; the balance is Fe and unavoidable impurity elements. Among them, (30C+0.5Mn)×100=6.1≥4.4, B / S=3.5≥3, 0.3≤Ti / Mo≤0.6.
[0037] A method for preparing high-strength and toughness fine-grained multiphase wear-resistant steel comprises the following steps: (1) Smelting process route: hot metal KR desulfurization pretreatment → top and bottom combined blowing converter smelting → LF refining → RH furnace vacuum refining (treatment for 16 min at vacuum degree ≤ 1 mbar, pure degassing time 12 min).
[0038] (2) Continuous casting process route: The overheat of the tundish in the continuous casting process is controlled at 22°C, and the casting is protected throughout the process. The casting machine pulling speed is 1.15m / min, and the fluctuation is controlled within ±0.1m / min. The liquid level fluctuation during the casting process is controlled to ±0.2mm, and the crystallizer is electromagnetically stirred; dynamic light pressure reduction technology is used during the continuous casting process. During the continuous casting process, light pressure reduction is used from the solid phase ratio of the center of the billet to 0.65. The initial pressure reduction rate is 1.0mm / m, and the pressure reduction rate is dynamically increased at a rate of 0.05mm / m until the end of the solidification of the billet. The pressure reduction is 6mm. The billet thickness is 280mm, and the billet thickness / the final rolling thickness of the steel plate is 5, and the billet is slowly cooled in the slow cooling pit for 50h.
[0039] (3) Heating process route: The casting time in the furnace is 330 min, and it is heated in the temperature range of 1220~1240℃ for 40 min.
[0040] (4) Rolling process: The rough rolling + finishing rolling mode is adopted. The rough rolling start temperature is 1167℃. The rough rolling is performed in 3 passes. The longitudinal and transverse rolling methods, reduction amount and reduction rate of the first to third passes are as follows: the first pass is transverse rolling: 63mm, the reduction rate is 22.5%, the second pass is transverse rolling: 47mm, the reduction rate is 21.7%, the third pass is longitudinal rolling: 34mm, the reduction rate is 20%, and the intermediate billet thickness after rough rolling / the final thickness of the steel plate is The degree is 3.4; after the intermediate billet is kept at temperature for 8s, it is sprayed with high-pressure water on the frame to quickly cool down and enter the finishing rolling. The starting temperature of the finishing rolling of the steel plate is 924℃, and the final rolling temperature of the finishing rolling is 846℃. The intermediate billet is rolled to a finished product thickness of 40mm by 5 passes of reciprocating rolling on a single frame. During this process, the reduction of each pass is 32mm for the first pass, 24mm for the second pass, 18mm for the third pass, 13mm for the fourth pass, and 9mm for the fifth pass.
[0041] (5) Cooling process route: Online water cooling is adopted, the starting cooling temperature is 832℃, the final cooling temperature is 210℃, the cooling rate is 46℃ / s, and then the steel plate stack is cooled to room temperature.
[0042] (6) Heat treatment process route: The heat treatment adopts the process of quenching + low-temperature tempering. The steel plate is slowly heated to 560°C, then heated to 830°C at a heating rate of 70°C / min, and kept in this temperature range for 40 minutes. Then it is quickly cooled to 270°C at a cooling rate of 42°C / s, and air-cooled to room temperature. The steel plate is then straightened, finished, spray-numbered, and sampled for performance inspection.
[0043] The high-strength and toughness fine-grained multiphase wear-resistant steel prepared in Example 1 has the following mechanical properties: surface Brinell hardness: 442 HBW, and the hardness of the core of the steel plate in the thickness direction of the steel plate is 410 HBW, tensile strength: 1326 MPa, yield strength ratio: 0.8, elongation after fracture: 13.2%, and -40°C impact absorption energy: 50.7 J.
[0044] Figure 1 The scanning electron microscope photo of the wear-resistant steel obtained in Example 1 shows that the matrix structure of the finished steel plate is 95.3% tempered martensite + 3.2% residual austenite + 1.5% carbide. The tempered martensite structure is fine and dense, and the lath width of the tempered martensite is 0.32±0.17μm. A large number of carbonitrides are dispersed in the martensite matrix, most of which are fine particles, flakes or short rods, with a size of about 6~130nm; in addition, there are a small amount of coarse carbonitrides distributed at the original austenite grain boundary position, with a size of about 0.35μm.
[0045] Figure 2This is a transmission electron microscope photograph of the wear-resistant steel obtained in Example 1. It can be seen that an extremely fine retained austenite film is distributed in the martensite matrix, and the film width is 0.018±0.006μm.
[0046] Example 2 A high-strength and toughness fine-grained multiphase wear-resistant steel, comprising the following chemical components in weight percentage: C: 0.18%, Si: 0.3%, Mn: 1.6%, Ti: 0.05%, Cr: 0.25%, Mo: 0.12%, Al: 0.04%, P: 0.005%, S: 0.001%, N: 0.0016%, H: 0.00015%, B: 0.0036%; the balance is Fe and unavoidable impurity elements. Among them, (30C+0.5Mn)×100=6.2≥4.4, B / S=3.6≥3, 0.3≤Ti / Mo≤0.6.
[0047] A method for preparing high-strength and toughness fine-grained multiphase wear-resistant steel comprises the following steps: (1) Smelting process route: hot metal KR desulfurization pretreatment → top and bottom combined blowing converter smelting → LF refining → RH furnace vacuum refining (treatment for 15 min under vacuum degree ≤ 1 mbar, pure degassing time 12 min) (2) Continuous casting process route: The overheat of the tundish in the continuous casting process is controlled at 24°C, and the casting is protected throughout the process. The casting machine pulling speed is 1.2m / min, and the fluctuation is controlled within ±0.1m / min. The liquid level fluctuation during the casting process is controlled to ±0.2mm, and the crystallizer is electromagnetically stirred; dynamic light pressure reduction technology is used during the continuous casting process. During the continuous casting process, light pressure reduction is used from the solid phase ratio of the center of the billet to 0.65. The initial pressure reduction rate is 0.9mm / m, and the pressure reduction rate is dynamically increased at a rate of 0.06mm / m until the end of the solidification of the billet. The pressure reduction is 6mm. The billet thickness is 280mm, and the billet thickness / the final rolling thickness of the steel plate is 12.5, and the billet is slowly cooled in the slow cooling pit for 50h.
[0048] (3) Heating process route: The casting time in the furnace is 340 min, and it is heated in the temperature range of 1220~1240°C for 45 min.
[0049] (4) Rolling process: The rolling mode of rough rolling + finishing rolling is adopted, the starting rolling temperature of rough rolling is 1170°C, the rolling method of longitudinal and transverse rolling is adopted in the rough rolling stage, and the rough rolling is performed for 5 passes. The longitudinal and transverse rolling methods, reduction amounts and reduction rates of the first to fifth passes are as follows: the first pass is transverse rolling: 56 mm, reduction rate: 20%, the second pass is transverse rolling: 48 mm, reduction rate: 21.4%, the third pass is longitudinal rolling: 36 mm, reduction rate: 20.5%, the fourth pass is longitudinal rolling: 28 mm, reduction rate: 20%, the fifth pass is longitudinal rolling: 2 3mm, reduction rate: 20.5%, the intermediate billet thickness after rough rolling / the final rolling thickness of the steel plate is 5.6; after the intermediate billet is kept at temperature for 8s, it is sprayed with high-pressure water on the frame to quickly cool down and enter the finishing rolling. The starting rolling temperature of the steel plate finishing rolling is 985°C, and the final rolling temperature of the finishing rolling is 855°C. The intermediate billet is rolled to a finished product thickness of 16mm by 5 passes of reciprocating rolling on a single frame. During this process: the first pass: 27mm, the second pass: 19mm, the third pass: 14mm, the fourth pass: 8mm, and the fifth pass: 5mm.
[0050] (5) Cooling process route: online water cooling is adopted, the starting cooling temperature is 825°C, the final cooling temperature is 220°C, the cooling rate is 50°C / s, and then the steel plate stack is cooled to room temperature.
[0051] (6) Heat treatment process route: The heat treatment adopts the process of quenching + low-temperature tempering. The steel plate is slowly heated to 560°C, then heated to 830°C at a heating rate of 76°C / min, and kept in this temperature range for 25 minutes. Then, it is quickly cooled to 272°C at a cooling rate of 50°C / s, and air-cooled to room temperature. The steel plate is then straightened, finished, spray-numbered, and sampled for performance inspection.
[0052] The high-strength and toughness fine-grained multiphase wear-resistant steel prepared in Example 2 has the following mechanical properties: surface Brinell hardness: 458 HBW, and the hardness of the core of the steel plate in the thickness direction of the steel plate is 415 HBW, tensile strength: 1365 MPa, yield strength ratio: 0.76, elongation after fracture: 13.6%, -40°C impact absorption energy: 76.2 J.
[0053] Figure 3 The scanning electron microscope photo of the wear-resistant steel obtained in Example 2 shows that the matrix structure of the finished steel plate is 93.8% tempered martensite + 4.9% retained austenite + 1.5% carbide. The tempered martensite structure is fine and dense, and the lath width of the tempered martensite is about 0.25±0.18μm. A large number of granular, flake or short rod-shaped carbonitrides are dispersed in the martensite matrix, most of which are extremely small <20nm, and a small number of larger sizes are between 21nm and 180nm.
[0054] Figure 4This is a transmission electron microscope photograph of the wear-resistant steel obtained in Example 2. It can be seen that the retained austenite is distributed in the martensite matrix, the width of the very fine retained austenite film is about 0.019±0.004μm, and the size of some blocky retained austenite is 0.05~0.18μm.
[0055] Although the present invention has been described in detail with reference to the accompanying drawings and in combination with the preferred embodiments, the present invention is not limited thereto. Without departing from the spirit and essence of the present invention, a person of ordinary skill in the art may make various equivalent modifications or substitutions to the embodiments of the present invention, and these modifications or substitutions shall be within the scope of the present invention. Any person of ordinary skill in the art may easily think of changes or substitutions within the technical scope disclosed by the present invention, and these shall be within the scope of protection of the present invention.
Claims
1. A high-strength and toughness fine-grained multiphase wear-resistant steel, characterized in that: The chemical composition includes the following weight percentages: C 0.12% - 0.20%, Si 0.1% - 0.4%, Mn 1.6% - 2.0%, Ti 0.045% - 0.08%, Cr 0.15% - 0.3%, Mo 0.05% - 0.16%, Al 0.02% - 0.05%, P ≤ 0.01%, S ≤ 0.003%, N ≤ 0.002%, H ≤ 0.0002%, B 0.002% - 0.004%, where (30C + 0.5Mn) × 100 ≥ 4.4, B / S ≥ 3, 0.3 ≤ Ti / Mo ≤ 0.6, and the balance is Fe and inevitable impurities.
2. A high-strength and toughness fine-grained multiphase wear-resistant steel as claimed in claim 1, characterized in that: It has the following mechanical properties: the surface Brinell hardness is 435 - 470 HBW, and the hardness attenuation from the surface to the core in the thickness direction of the steel plate is ≤ 2 HBW / cm; the tensile strength of the steel plate is 1300 - 1400 MPa, the yield ratio is ≤ 0.82, and the elongation after fracture is ≥ 12%; the relationship between the impact absorption energy of the steel plate at -40°C and the finished steel plate thickness h is as follows: when 12 mm ≤ h ≤ 20 mm, the impact absorption energy of the steel plate at -40°C is ≥ 75 J; when 20 mm < h ≤ 28 mm, the impact absorption energy of the steel plate at -40°C is ≥ 64 J; when 28 mm < h ≤ 36 mm, the impact absorption energy of the steel plate at -40°C is ≥ 56 J; when 36 mm < h ≤ 42 mm, the impact absorption energy of the steel plate at -40°C is ≥ 48 J.
3. The high-strength and toughness fine-grained multiphase wear-resistant steel according to claim 1, characterized in that: It has the following microstructure: 93% - 96% tempered martensite + 3% - 5% retained austenite + 1% - 2% carbides. The tempered martensite is in lath shape, the austenite is in film shape, and some carbides are dispersed in the tempered martensite matrix.
4. A method for preparing the high-strength and toughness fine-grained multiphase wear-resistant steel according to claim 1, characterized in that: It includes the steps of smelting, continuous casting, heating, rolling, cooling, and heat treatment in sequence; the heat treatment step adopts the quenching + low-temperature self-tempering process: quenching includes first heating the steel plate to 500 - 600°C, then heating it to 820 - 835°C at a rate of ≥ 60°C / min for holding, and subsequently cooling it to 260 - 280°C at a rate of ≥ 40°C / s; the low-temperature self-tempering is to complete the low-temperature self-tempering process of the steel plate by using its own residual heat after quenching.
5. The method for preparing high-strength and toughness fine-grained multiphase wear-resistant steel according to claim 4, characterized in that: The smelting step includes the KR desulfurization pretreatment of hot metal, top-bottom combined blowing converter smelting, LF refining, and RH furnace vacuum refining; in the RH furnace vacuum refining step, the treatment time is ≥ 12 min under the condition of a vacuum degree ≤ 1 mbar, and the pure degassing time is ≥ 9 min.
6. The method for preparing high-strength and toughness fine-grained multiphase wear-resistant steel according to claim 4, characterized in that: The continuous casting step includes controlling the superheat of the tundish at 12 - 25°C, carrying out full protection casting, with the target casting speed of the caster being 0.85 - 1.35 m / min, the casting speed fluctuation being controlled within ± 0.1 m / min, controlling the liquid level fluctuation during casting within ± 0.2 mm, and adopting mold electromagnetic stirring. The thickness of the slab is 270 - 320 mm, and the slab thickness / the final rolling thickness of the finished steel plate ≥ 7.5; during continuous casting, soft reduction is started when the solid fraction at the center of the slab is 0.65, the initial reduction rate is 0.8 - 1.2 mm / m, and the reduction rate is dynamically increased at a rate of 0.04 - 0.06 mm / m until the end of solidification, and the reduction amount is 2 - 8 mm.
7. The method for preparing high-strength and toughness fine-grained multiphase wear-resistant steel according to claim 4, characterized in that: The heating step includes placing the continuously cast billet in a heating furnace for heating. The residence time of the billet in the furnace is 1.1t min + 20 - 30 min, where t is the value of the billet thickness. The billet is heated within the temperature range of 1200 - 1260 °C for 40 - 45 min.
8. The method for preparing high-strength and toughness fine-grained multiphase wear-resistant steel according to claim 4, characterized in that: The rolling step includes rough rolling and finish rolling. The rough rolling starting temperature is 1140 - 1180 °C. The cross - and longitudinal rolling method is adopted in the rough rolling stage. The large reduction mode is adopted during the rolling process of 2 - 6 passes, and the reduction rate per pass is maintained at 16% - 30%. The ratio of the thickness of the intermediate billet after rough rolling to the final thickness of the finished steel plate ≥ 3.
2. After the intermediate billet is held for 3 - 12 s, it enters the finish rolling after being cooled by high - pressure water spraying on the stand. When the finished thickness is h and 12 mm ≤ h ≤ 28 mm, the finish rolling starting temperature of the steel plate is 980 - 1000 °C, and the finish rolling ending temperature is 850 - 870 °C. When 28 mm < h ≤ 42 mm, the finish rolling starting temperature of the steel plate is 910 - 930 °C, and the finish rolling ending temperature is 830 - 850 °C. The reduction rates of the last pass and the pass before the last pass are ≥ 12% and ≥ 18% respectively.
9. The method for preparing high-strength and toughness fine-grained multiphase wear-resistant steel according to claim 4, characterized in that: The cooling step adopts online water cooling. The starting temperature of the online water cooling ≥ 820 °C, the ending temperature ≤ 240 °C, and the cooling rate ≥ 40 °C / s.
10. The method for preparing high-strength and toughness fine-grained multiphase wear-resistant steel according to claim 4, characterized in that: The heat preservation time is 0.6 h + 0 - 20 min, where h is the value of the thickness of the finished steel plate.
Citation Information
Cited By
Ultrahigh-toughness wear-resistant maritime work steel plate based on gradient structure design and manufacturing method thereof
CN121046730A
An ultra-high strength and toughness wear-resistant marine steel plate based on gradient structure design and a manufacturing method thereof
CN121046730B